Internalisasi Pendidikan Nilai Melalui Pembelajaran Terintegrasi di MAU Darul Ulum Step-2 IDB Peterongan-Jombang - Purwaningrum, Septiana (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2013)
The research aims at describing the internalization of value education through integrated instruction at MAU-DU STEP-2 IDB Peterongan-Jombang. The data were collected through participant observation, in-depth interview, and documentation. The results show that the internalization of value education was done through integrated instruction of religious and common knowledge, technology, and language. Inductive instruction was used. The instructional media were printed and electronic media and realia. The evaluation includes Â UHT, UTS, UAS, UN, and TA. In addition, some barriers were also found: insufficient classroom and time; and supporting factors are complete laboratory, cooperation with Kemenag and IDB, support from alumni and parents, and conducive environment at the school.